Russia-ASEAN Summit 2016: Improvement For The Better Strategic Partnership - Umagapi, Juniar Laraswanda (Jurnal Ilmiah Hubungan Internasional, 2017)
AbstractThis article tries to elaborate the impact for the cooperation between ASEAN-Russia in economic and political security. How the ways to increase their bilateral relations and bring positive impacts for both countries. ASEAN is often regarded as the paragon case of successful regional security cooperation and attributes its achievement to economy, socialâcultural and political-security. In the recent years, ASEAN try to create many external relations with another country and Russia is one of them. ASEAN want to make a mutual relationship with others and solve the regional issue happen in many countries. Economy and political security will be the main issue for this cooperation. ASEAN and Russia start their bilateral relation for a long time ago but economic relations like trade is still low but they try hard to progress. After ASEAN summit 2016 in Sochi, Russia on 19-21 May a lot of agreement have been signed and people looking forward for the impact of this partnership.Keywords: ASEAN; strategic partnership; security; economy; political; ASEAN-Russia Summit 2016; sochiAbstrakArtikel ini mencoba untuk menguraikan dampak kerjasama antara ASEAN-Rusia dalam bidang keamanan ,ekonomi dan politik. Bagaimana cara meningkatkan hubungan bilateral antar kedua negara dan membawa dampak positif bagi kedua negara. ASEAN sering dianggap sebagai kasus paragon dari suksesnya kerjasama keamanan regional dan memberikan kontribusi prestasinya di bidang ekonomi, sosial budaya dan keamanan politik. Dalam beberapa tahun terakhir, ASEAN mencoba menciptakan banyak hubungan eksternal dengan negara lain dan Rusia adalah salah satunya. ASEAN ingin menjalin hubungan timbal balik dengan negara-negara lain dan memecahkan masalah regional yang terjadi di banyak negara. Ekonomi dan keamanan politik akan menjadi isu utama untuk kerja sama ini. ASEAN dan Rusia memulai hubungan bilateral mereka untuk waktu yang lama namun hubungan ekonomi seperti perdagangan masih rendah karena itu mereka berusaha keras untuk berkembang. Setelah KTT ASEAN 2016 di Sochi, Rusia pada tanggal 19-21 Mei banyak kesepakatan telah ditandatangani dan banyak pihak menantikan dampak dari kemitraan ini.Kata Kunci: ASEAN; kemitraan strategis; keamanan; ekonomi: politik; KTT ASEAN-Rusia 2016; sochi